Tujuan dari penelitian ini adalah sebagai upaya aplikasi starter probiotik dari yogurt dan L. plantarum yang ada di pasaran dalam pembuatan sosis fermentasi yang sehat agar dapat diaplikasikan secara praktis dan mudah sehingga perlu mengetahui kualitas so - Agus Susilo; Eny Sri Widyastuti; Herly Evanuarini; Mulia Winirsya Apriliyani (Jurnal Penelitian Pendidikan IPA, 2023)
This research is related to the application of probiotic yogurt starter and L. plantarum. The purpose of this study is related to know and comparing the quality of fermented sausages in terms of pH, aw, water content, protein content, fat and ash content so that they become healthy food and practical and easy to manufacture. Treatment with differences in the use of yogurt starter and L. plantarum respectively 0%, 1%, 2%, and 3%. The results showed that the use of yogurt starter and L. plantarum each did not provide a significant difference (P>0.05) for the value of pH, aw, moisture content, protein content, fat content, and ash content. it can be concluded that by comparison of the use of yogurt starter (which contains several types of bacteria) with L. plantarum each has differences in pH, aw, moisture content, protein content, fat content, and ash content but all are still in accordance with SNI.